PRALE, estrategia didáctica para mejorar el lenguaje oral de los estudiantes de 3 años de la I.E 1591, Trujillo-2018 - Ramos Parimango, Yeniffer Yoselin (2019)
The pre-experimental research had as a general purpose to diagnose the level of oral language of the 3-year-old “B” children of the E.I. Nº 1591 “La casa del Niño” of the city of Trujillo in the year of 2018; using the T student._x000D_ To carry out the diagnosis of the level of oral language of the 3-year-old children “B”, the information was collected through the following instrument: Checklist. Taking into account the two dimensions of evaluation (linguistic and non-linguistic), which allowed us to discover the level of oral language in which the children of the sample group were. Twenty one boys and girls who were considered for this observation (only 19 of them were applied, due to the continuous absence of two children) constituted this group._x000D_ The analyzed and compared results showed us that the pre-test (table Nº 01), indicated that of the 19 3-year-old “B” students of the E.I. Nº 1591 “La casa del Niño” evaluated in the post-test, we can indicate that the 84% presented an “A” level (high level) of oral language, while the 16% represented a “B” level (low level). What evidenced that the oral language of the 3-year-old boys and girls had significant progress through the application of the PRALE program